Perlindungan Hukum Bidan dalam Tindakan Pemasangan Alat Kontrasepsi dalam Rahim (AKDR) di Puskesmas - Santa Lussia Yunica (Faculty of Law- Hang Tuah University, 2021)
Increasing population growth can be suppressed through the Family Planning (Keluarga Berencana/KB) program, one of which is the installation of uterine contraceptive devices (IUDs) by midwives at the Puskesmas. Juridically, the midwife has the authority to install an IUD. However, contraceptive failure often occurs, in which midwives can face criminal or civil lawsuits regarding the IUD insertion case. The method in this study is a normative juridical approach to the law (statue approach) and conceptual approach (conceptual approach). Related to the problem of IUD insertion failure, midwives are only responsible for the installation actions according to their competency standards. While the results of failures that may occur can not be accounted for because the transactions that occur between midwives and patients emphasize the maximum effort of the midwife. Minister of Health Regulation No. 28 of 2017 related to the Licensing and Implementation of Midwife Practices that discusses the rights and authority of midwives regarding contraception. To ensure legal certainty, clear regulations regarding the profession of midwife are set out in the Midwifery Law.